دراسة تأثير الفتحات على سلوك جدران القص المعدنية الصفائحية المختلطة - ناصر, عصام; لوحو, غاندي; طوالو, علي (Latakia University Journal -Engineering Sciences Series, 2018)
Early 1970s, the steel shear walls in buildings were used as resistant systems against lateral loads. However, their weakness on the fast buckling of the web plate forces the designer to use reinforced concrete layer at one or both sides of the steel shear walls. The resultant system, composite steel plate shear walls, are then utilized as efficient systems against lateral loads. In this paper, we investigated the position and dimensions of the rectangular opening on the performance of this complex system. To fulfill this aim, some models of composite shear wall with different opening surface and their location were considered and then analyzed using a pushover analysis by using SAP2000program to find the most criticalopening size and location, and investigating the effect of different opening types on composite shear wall dynamic behavior. The results show that by increasing the size of the opening surfacethe stiffness and load capacity characteristics will reduce. تستخدم جدران القص المعدنية منذ العام 1970 كأحد الأنظمة الانشائية لمقاومة الحمولات الجانبية في الأبنية المتعددة الطوابق. لكن وبسبب ضعف هذه الجدران من خلال تحنيبها بشكل سريع، عمد المصممون الى زيادة تقويتها من خلال إضافة لوح من البيتون المسلح من جهة واحدة أو من جهتي جدار القص المعدني وهذا ما سمي بجدار القص المعدني المختلط الذي استعمل مؤخرا كأحد الأنظمة الانشائية الفعالة في مقاومة الحمولات الجانبية. وقد تتطلب الشروط المعمارية في المبنى وجود فتحات ضمن جدران القص لذلك فان مساحة وموقع الفتحة له تأثير مهم على سلوك جدار القص. نحاول من خلال هذا البحث دراسة تأثير موقع وأبعاد الفتحة على أداء هذه الأنظمة الانشائية المركبة. ولتحقيق هذا الهدف تم تصميم مجموعة مختلفة من نماذج الجدران المختلطة مع فتحات وتمت عملية النمذجة والتحليل باستخدامpushover بمساعدة برنامجSAP2000بهدف إيجاد موقع وأبعاد الفتحة الحرجة وانعكاسها على سلوك الجدار. أظهرت النتائج أن زيادة ابعاد الفتحة وموقعها لها تأثير مهم على انخفاض قدرة تحمل وصلابة الجدار وانعكاس ذلك على مستوى أدائه عند تعرضه للحمولات الخارجية.